cDNA clone analysis of six co-regulated mRNAs encoding skeletal muscle contractile proteins. - Hastings, K E (1982)
A cDNA cloning approach was used to investigate muscle gene regulation during differentiation of cultured embryonic quail myoblasts. A cDNA clone library of cultured myofiber poly(A)+RNA was constructed and screened by colony hybridization with cDNA probes of myoblast and myofiber RNA. Twenty-eight myofiber-specific cDNA clones were identified and, by cross-hybridization analysis, these clones were found to represent, at most, 18 different myofiber-specific RNAs. Six of these RNAs were identified by sequence analysis of the cDNA clones. These six RNAs encode the contractile proteins alpha-actin, alpha-tropomyosin, myosin heavy chain, myosin light chain 2, troponin C, and troponin I. The embryonic muscle contractile protein sequences are identical with, or closely match, those of adult skeletal muscle proteins and include both fast fiber (myosin light chain 2 and troponin I) and slow fiber (troponin C) isotypes. RNA gel transfer hybridization analysis showed that the cellular abundances of these contractile protein mRNAs increase 20- to 30-fold or more during myoblast differentiation. These findings indicate that coordinate activation of contractile protein synthesis during myogenesis is controlled by mechanisms that direct the accumulation of contractile protein mRNAs rather than their translational utilization. Furthermore, with the possible exception of myosin heavy chain, the contractile protein genes expressed by cultured embryogenic muscle encode adult muscle proteins of both basal and slow fiber types, consistent with a co-activation-selective repression model of gene regulation during fiber type differentiation in developing skeletal muscle.